The Oxford handbook of the theory of international law - Orford, Anne; Hoffmann, Florian, 1972- (Oxford : Oxford University Press, 2016)
This Oxford handbook explores key questions and debates in international legal theory, offering new intellectual histories for the discipline, and providing fresh interpretations of significant historical figures, texts, and theoretical approaches.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 31, 2016). (viewed on September 21, 2016).
Keywords: International law -- Philosophy; International law; Law; International law